Respuesta :

Answer:

x=-7

Step-by-step explanation:

Answer:

x=7

Step-by-step explanation:

Simplifying

-1(8 + -3x) = 13

(8 * -1 + -3x * -1) = 13

(-8 + 3x) = 13

Solving

-8 + 3x = 13

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '8' to each side of the equation.

-8 + 8 + 3x = 13 + 8

Combine like terms: -8 + 8 = 0

0 + 3x = 13 + 8

3x = 13 + 8

Combine like terms: 13 + 8 = 21

3x = 21

Divide each side by '3'.

x = 7

Simplifying

x = 7